Eutectoid WxC embedded WS2 nanosheets as a hybrid composite anode for lithium-ion batteries. Issue 13 (1st July 2021) - Hussain, Sajjad; Faizan, Muhammad; Vikraman, Dhanasekaran; Rabani, Iqra; Ali, Basit; Kim, Hyun-Seok; Jung, Jongwan; Nam, Kyung-Wan
Abstract: A novel eutectoid structure, Wx C-embedded WS2 nanosheets hybrids composite, was developed by hydrothermal reaction followed by a carbonization process. The fabricated WS2 –Wx C hybrid nanosheets electrode was used for lithium-ion batteries as an anode material, and demonstrated the specific capacity of 272 mA h·g −1 at 0.01 A g −1 with enhanced rate competence and cycling behavior when compared with individual WS2 and W2 C electrode. While the large interlayer spacing in WS2 facilitates rapid Li + transport, the extremely high electronic conductivity of Wx C provides a highly conductive electron transfer pathway, which facilitates fast and reversible (de)lithiation reactions during charging and discharging. Further, these outcomes point the way for developing future eutectoid hybrid systems for advanced energy-storage applications.